Culture Change and Quality of Care Among High Medicaid Nursing Homes: Does Earlier Implementation Matter? - Latarsha Chisholm; Akbar Ghias; Rohit Pradhan; Justin Lord; Ganisher Davlyatov; Robert Weech-Madonado (Journal of Long-Term Care)
Context: High Medicaid nursing homes are under-resourced and associated with lower resident quality of care. Culture change initiatives, a movement to transition nursing homes to more home-like environments, are a potential process to improve residents’ quality of life and care.